The effect of Tabata training on increasing VO2max and arm muscle strength in athletes handball - Al Haq, Akmal Abdillah; Yuliastrid, Dita; Irawan, Roy Januardi; Nugraha, Testa Adi (Sriwijaya Journal of Sport, 2026)
Research Problems: Handball requires a combination of good physical fitness, speed, agility, and endurance. Optimal VO2Max is needed for athletes to maintain match performance, and must be supported by arm muscle strength to maximize passing and shooting quality. Tabata training, a form of HIIT training with a pattern of 20 seconds of high-intensity training and 10 seconds of rest in 8 sets, is effective in increasing VO2Max and arm muscle strength. However, the previous training method was considered too monotonous by athletes, so variations in movements, such as Tabat, were needed to maintain athlete motivation when doing it repeatedly. Research Objectives: to determine the effect of Tabata training on increasing VO2Max and arm muscle strength of handball athletes in Gresik Regency. Methods: With a quantitative research type and using a pre-experimental research method. The sample numbered 16 with certain criteria and with a purposive sampling technique. The measurement instruments used included the Multistage Fitness Test to measure VO₂Max and the Two-Hand Medicine Ball Put Test to measure arm muscle strength. Results: The data shows an increase in the average VO₂Max from 44.39 ml/kg/minute to 46.42 ml/kg/minute with a difference in increase of 2.03 ml/kg/minute and an increase in arm muscle strength from 5.01 meters to 5.42 meters with a difference in increase of 0.41 meters. Statistical tests with paired sample t-tests showed that the increase was significant (p <0.05). Conclusion: Tabata Training has a significant effect on increasing VO₂Max and arm muscle strength of Gresik Regency handball athletes.